SOSIALISASI PROGRAM KAMPUNG BAHARI TAMBAK LOROK SEMARANG - Nico Ariowibowo; Wiwid Noor Rakhmad (Interaksi Online, 2019)
Development carried out by the government has a function to build human resources and also build physical in an area. The development of Kampung Bahari Tambak Lorok is one of them, which has the aim of alleviating slums and prospering its citizens. This study aims to describe the process of socialization, involvement and involvement of the Tambak Lorok community and to know the inhibiting and supporting factors. The research method uses descriptive qualitative with primary data sources from interviewees as many as 11 people, secondary data taken from relevant documents, as for data analysis using case studies with pattern matching, simple pattern patterns. The results of the study show: (1) The socialization starts with planning the concept first and the implementation is divided into 3 types of activities (2) The involvement and involvement of the Tambak Lorok community is very limited (3) The inhibiting factors and supporting more problems in non-technical matters, namely concerning characteristics of coastal communities.